An 'improbable Paris-Berlin-Commission triangle': usages of Europe and the revival of EU defense cooperation after 2016. Issue 3 (3rd April 2021) - Béraud-Sudreau, Lucie; Pannier, Alice
ABSTRACT: Since mid-2016, several policy initiatives have signaled a move forward in European defense co-operation, with a return to the EU as the vehicle of choice. The change is notable, considering the prior ineffectiveness of the EU's defense cooperation initiatives, and the trends observed in the past decade where member states opted for co-operation outside EU frameworks. Several crises and strategic changes, including Russia's annexation of Crimea, Brexit, and US retrenchment from Europe make the choice for more EU defense appear as self-evident. However, far from an obvious cause-effect relationship, a look at the actors and processes behind decision-making reveals that it is only through a conjunction of separate but converging strategies from EU and member states actors, that a 'window of opportunity' was opened and seized in 2016. Our analysis examines the distinct motives and strategies, especially, of the commission, Germany and France, in pursuing their agendas for European defense.